Compendium of Climate-smart Agriculture Technologies and Practices - Bhusal, Aastha; Khatri, Laxman; GC, Sagar; Mandal, Indeshwar; Bhatt, Bhagwati P; Pudasaini, Niranjan; Katuwal, Yogendra; Mishra, Sujan; Gautam, Anita; Shiwakoti, Tejaswee; Dhakal, Bishnu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Nepal is a vulnerable country to the impacts of climate change. The adverse effects of climate change have decreased agricultural production and productivity. Therefore, technologies and strategies to develop resilience agriculture and increased agriculture productivity are urgently needed to create climate-smart technologies and help the existing technologies to adapt to climate change. This compendium presents climate-smart agriculture (CSA) technologies and interventions for enhancing food security with adaptation and mitigation as co-benefits. CSA involves smart farming practices and strategies that help develop resilience agriculture, increase crop and livestock productivity, reduce greenhouse gas emissions, and enhance food security goals. This compendium has been developed for extension workers to support up-scaling climate-smart technologies and build climate resilience villages that enhance food, nutrition, and income, mainly for marginal communities striving in marginal areas.